Rada Federalna i Prezydent Konfederacji Szwajcarskiej. Specyfika i ewolucja rozwiązań kreowania władzy wykonawczej - Musiał-Karg, Magdalena; Duda, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Switzerland is an example of a state that has adopted specific solutions as regards the election and execution of executive power, which has generated the common conviction that the Swiss Confederation is among the most solid democracies in the world. Recent years have shown, however, that political practice has brought about a significant evolution of Swiss solutions as the distribution of power in the parliament has resulted in the abolition of the ‘magical formula’ that guaranteed the great (and stable) government coalition, and the emergence of initiatives aiming at changing the principles along which executive power is elected in Switzerland. The purpose of considerations presented in this paper is to analyze the specific character of how the executive institutions function in the Swiss Confederation, answer the question of what directions the changes to the composition of the Federal Council are taking, as well as address the directions of evolutionary changes to the principles of electing the members of the Swiss government.